Analysis of model and data uncertainties for the failure of adhesive bonds in composite materials. Issue 1 (25th January 2021) - Drieschner, Martin; Gruhlke, Robert; Petryna, Yuri; Eigel, Martin; Hömberg, Dietmar
Abstract: This study has been performed within the research project MuScaBlaDes "Multi‐scale failure analysis with polymorphic uncertainties for optimal design of rotor blades" as part of the DFG Priority Programme (SPP 1886) "Polymorphic Uncertainty Modelling for the Numerical Design of Structures" started in 2016. Stress concentrations in adhesive bonds of a composite structure influence the structural integrity and can initiate the overall failure. Their numerical prediction always depends on present model and data uncertainties. For that, the development of an efficient numerical model and the role of the quality of data is presented. The assessment of the numerical models is shown by comparing predicted strains to measured ones.